Strengthening Logistics Defense and Digital Technology to Optimize Humanitarian Operation Support in Indonesia - Shoraya Lolyta Octaviana; Zainal Abidin Sahabuddin; Totok Imam Santoso; Guntur Eko Saputro (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This research discusses the strategy of strengthening defense logistics through the use of digital technology in supporting humanitarian operations by the Indonesian Military. Background departs from the fact that defense logistics so far is often understood to be limited to technical functions, even though it has a strategic role in maintaining national resilience. The focus of research is directed at multidimensional barriers, which include overlapping regulations, separatist threats, limited resources, low public participation, weak information literacy, and infrastructure constraints and geographical conditions of the island. The research method uses a qualitative approach with PMESII frame combined with data analysis through NVIVO 12. The results show the need for defense logistics transformation into a strategic system based on digital technology with a risk management approach that emphasizes aspects of planning, distribution, transportation, efficiency, and effectiveness through the support of information systems, satellite technology and UAVs, and geographical mapping. This finding confirms that the transformation of digital technology can improve efficiency, transparency, and responsiveness while strengthening legitimacy and public trust. Further research is advised to test the effectiveness of the Digital Technology Based Defense Logistics Model through empirical case studies and disaster scenario simulations and conflicts in Indonesia.